New species of Macrolycus Waterhouse, 1878 from China and Laos, with a checklist of the genus (Coleoptera: Lycidae) - Li, Yun; Bocak, Ladislav; Pang, Hong (Zootaxa, 2012)
Eight new Macrolycus are described: M. luteus sp. nov., M. mucronatus sp. nov., M. muyuensis sp. nov., M. quadrifidus sp.nov., M. rubineus sp. nov., M. venustus sp. nov. from China and M. extrusus sp. nov., M. ligulatus sp. nov. from Laos. Macro-lycus testaceicollis var. notaticollis Pic, 1935 is elevated to M. notaticollis Pic, 1935, stat. nov. General appearance of the holo-types, male genitalia and important external characters are illustrated. Macrolycus dotatus Kleine, 1925 is reported from Laosfor the first time. A key to the Macrolycus species from Laos, Southeastern and Central China and a checklist of the genus Macrolycus are provided.